HIGH-FAT DIET IN THE PERI-PUBERTAL PERIOD PROGRAMS CARDIOVASCULAR DYSFUNCTION IN ADULT MALE WISTAR RATS - Vanusa Guedes Ribeiro, Maiara; Rebeka F. Oliveira, Anna; Natália C. Peres, Maria; Piovan, Silvano; A. Ferreira, Lucas; M. Gomes, Rodrigo; Cezar F. Mathias, Paulo; Gemima Palma Rigo Wutzow, Kesia (Arquivos do Mudi, 2023)
Stress during peri-pubertal period can determine no communicable disease in adulthood. This study aims to evaluate whether high fat diet exposure during adolescence induces long-term cardiovascular dysfunctions. The ethic committee approved the animal protocol nº 1527130815. Wistar rats, 30-days-old, were feed to a high fat diet (HFD, 35% lard w/w) until 60-days-old, then fed a normal fat diet for a further 60 days dietary recovery. Control animals ate normal fat diet throughout life. Body weight and food intake were evaluated weekly. At PN120, cardiovascular and histological analysis were done. Student´s T test were applied. PN120, feed by HFD during adolescence increase systolic and diastolic blood pressure (upper 10% and 4%, respectively; p <0.05 and p <0.005). Using ganglionic blocker, hexamethonium (30 mg/kg, iv), blood pressure was greater in the HFD rats (26%; p <0,01). Increased perivascular and interstitial fibrosis (42% and 62% respectively; p<0,01 and p<0,001) were observed in the HFD rats, accompanied by a left ventricular hypertrophy (29%; p<0,001). Rats who were fed with HFD during peri-pubertal age present hypertension, hyperactivity of the vascular sympathetic nervous system and morphological cardiac alterations in adulthood. Current study remarks that adolescence is a plastic phase which permit to programs diseases later in life.